2019
DOI: 10.1002/dmrr.3119
|View full text |Cite
|
Sign up to set email alerts
|

Predicting ulcer‐free survival using the discriminative value of screening test locations

Abstract: Background Current guidelines recommend screening the feet of diabetic subjects with a 10‐g monofilament or tuning fork. We investigated which tests and locations on the feet have the best predictive value regarding 1‐year ulcer‐free survival in diabetic subjects participating in the prospective Rotterdam Diabetic Foot Study. Methods Decision tree analysis was used to predict ulcer‐free survival based on responses from individual test locations (monofilaments on 10 sites, vibration sense was tested on both hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Moreover, the multisensory modalities included in the RDF‐39 are reflected in the decision tree that was developed using modern statistical techniques. Decision tree analysis has been demonstrated useful in item reduction of questionnaires and test batteries and has been used in different fields of medicine . Several caveats relating to our study are important to highlight.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the multisensory modalities included in the RDF‐39 are reflected in the decision tree that was developed using modern statistical techniques. Decision tree analysis has been demonstrated useful in item reduction of questionnaires and test batteries and has been used in different fields of medicine . Several caveats relating to our study are important to highlight.…”
Section: Discussionmentioning
confidence: 94%
“…However, thresholds and cut‐off values on how many test sites to be used for predicting, for example, first‐onset DFU, are often conjectured . A recent study using prospective RDF study data showed that particular sites of monofilament and vibratory testing outperformed composite scores of tuning fork (up to four test sites) and 10‐g monofilaments (up to 10 test sites) in the prediction of ulcer‐free survival . It is the combination of sensory test and test site that allows for staging of sensory loss, according to recently developed grading scales, with both test and test site having predictive properties regarding the degree of sensory loss observed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple clinical tests are available to detect signs of peripheral sensory neuropathy and include tests of loss of touch sensation (primarily 10 g monofilament). The use of tests of touch sensation has been shown to link to risk of the future development of new DFUs . Attention must be drawn, however, to there being no consistent guidance on which sites on the foot should be tested, how many should be tested and how many missing points of sensation constitutes abnormality.…”
Section: The Use Of Tests In Assessing Risk Of Dfu In People With Diamentioning
confidence: 99%
“…The use of tests of touch sensation has been shown to link to risk of the future development of new DFUs. [4][5][6] Attention must be drawn, however, to there being no consistent guidance on which sites on the foot should be tested, how many should be tested and how many missing points of sensation constitutes abnormality. Resulting inconsistencies undermine the interpretation of such tests in everyday clinical practice.…”
Section: Tests For Neuropathy In Everyday Clinical Practicementioning
confidence: 99%